DESIGN OF EXPERT SYSTEM FOR IDENTIFY OF ANXIETY DISORDERS USING FORWARD CHAINING - Finanta Okmayura; Vitriani Vitriani; Melly Novalia (Jurnal Riset Informatika, 2021)
Anxiety is an excessive anxiety disorder in psychology. People are basically not aware that they may have symptoms of this anxiety disorder in each of them. And if not treated as soon as possible can interfere with a person's psychological condition. It may seem trivial but this disorder can reduce performance so that it has an impact on a person's life. To overcome this problem, we need an expert system that can identify anxiety disorders using a forward chaining algorithm. This system is designed using UML (Unified Modeling Language) diagrammatic modeling. The purpose of this UML modeling is to describe the user's needs for the system and what things can be done by the system, so that with this UML modeling the entire system picture can be seen. The UML modeling for the expert system for early identification of anxiety disorders with the forward chaining algorithm is expected to be a tool that can assist the system creation process, where people can check whether they suffer from anxiety disorders or not to consult a psychologist.